Slavery and Kant’s Doctrine of Right - Huaping Lu-Adler (Journal of Modern Philosophy)
In the 1780s through the end of 1790s, Kant made various references to slavery (in its different forms) and the transatlantic slave trade in the context of his political philosophy or philosophy of right. He thereby had opportunities at least to articulate a normative critique of the race-based chattel slavery or Atlantic slavery and the associated slave trade qua (legalized) institutions. But he did neither. This normative silence about the institutions of Atlantic slavery and the slave trade points to certain limitations of Kant's political philosophy, limitations that might have made it theoretically difficult for him to figure out exactly what to do about those institutions as entrenched political realities.